Comparison of clinical practice guidelines methods to reach diagnostic test recommendations regarding diagnostic laparoscopy for endometriosis: A scoping review. - Frank Zela-Coila; Carlos Quispe-Vicuña; Janeth N Nuñez-Lupaca; Milagros Aparicio-Curazi; Sergio Goicochea-Lugo (PLoS ONE, 2024)
Introduction Although Clinical Practice Guidelines (CPG) highlight that laparoscopy is often used in the treatment of endometriosis, its diagnostic usefulness is not fully defined. Our objective was to evaluate the quality of CPGs for endometriosis that address the use of diagnostic laparoscopy in reproductive age women, and describe the recommendations and methods used to assess diagnostic test questions. Methods A comprehensive search of 5 databases (Trip Database, MEDLINE/PubMed, Web of Science, SCOPUS, and EMABSE) and websites of guideline development organizations and compilers was conducted from 2017 to 2023. A descriptive analysis of the recommendations was performed and the quality of the guidelines was assessed using the AGREE-II instrument. Results Four CPGs were included in the review, all exhibiting adequate methodological quality (scores ranging from 66.7% to 91.0%). Regarding the use of laparoscopy for endometriosis diagnosis, discrepancies in recommendations were observed. Two guidelines advised against it, one recommended either laparoscopy or medical empirical treatment, and one favored its use. GRADE guidance was employed for evidence assessment, but only one guideline transparently reported the certainty of evidence and the evidence-to-decision framework process. Conclusions Variability in recommendations among different CPGs were found. To keep in mind, discrepancies arise from differing prioritizations of the assessment of clinical impact in patient important outcomes and methodological approaches. This underscores the need for more standardized and transparent guideline development processes, particularly in addressing the clinical utility of diagnostic tests.